Profitability of Swedish Red and White × Holstein crossbred cows compared with purebred Holstein cows - Pipino DF; Lopez-Villalobos N; Hickson RE; Cabrera VE; Balzarini M; Piccardi M (Elsevier Inc. on behalf of the American Dairy Science Association, 2024)
An economic analysis was performed using a bioeconomic simulation model based on production, reproduction and longevity indicators to compare the profitability (net income per cow) of Swedish Red and White × Holstein (S × H) cows and pure Holstein (H) cows in commercial dairy farms of the center-south of Córdoba province, Argentina. The reproductive events analyzed in the model were pregnancy, calving and abortion. The longevity events were culling, sale and death. The lactation curve for each cow was modeled with a lactation function. Estimations were made for the first, second, and third and later lactations. Incomes were from milk, culled cows and calves. Costs were from feeding, reproductive program and replacement heifers. The reproductive cost of a H cow per year was greater than that of a S × H crossbred cow (USD 6.3). The replacement costs were also higher in pure H cows than in S × H cows (USD 67.8). The revenues from the sale of calves (USD 12.1) and milk production minus the feed cost (USD 8.2) were greater for S × H cows than H cows. Hence, the S × H cows generated a greater total profit (USD 94.4) per cow per year than H cows. The present results show that, in the studied production systems, S × H crossbred cows are more profitable than H cows.
Keywords: bioeconomic model; crossbreeding; economic analysis; simulated dairy farm